Synthesis And Characterization Magnetic Thermoelectric Materials of Bi2-xPbxSr2Co2Oy - AKBAR A. (NIM 10505047), TAUFIK
Ideal characteristics of thermoelectric material are high figure of merit, indicated by low resistivity, low thermal conductivity, and high Seebeck coefficient. Misfit compounds based cobalt oxide have been known exhibit large thermopower for example in [Bi0,87SrO2]2[CoO2]1,82 compound. In order to study effect of partial substitution Bi by Pb on termoelectric Bi-based cobaltates material, Bi2-xPbxSr2Co2Oy with x = 0, 0.5, 1.0, 1.5 dan 2.0 have been prepared in this research by solid state reaction process using precursors of Bi2O3, SrCO3, Pb3O4 and Co3O4. The precursors were calcinated in air at 800oC for 10 hours, followed by sintering in air at various temperatures for 20 hours. The XRD data indicated the crystal structures underwent slight modification as a result of Pb substitution for Bi. Resistivity measurement performed on the sample with x = 0 and 2 in the temperature range from 50 K to 300 K shows insulating behavior. The measured value of the resistivity shown that Pb substitution for Bi increase the electric conductivity. Further measurements of seebeck coefficient and thermal conductivity are required to determination of the material's figure of merit.